Evaluation of Analytical Agreement Between High-Performance Liquid Chromatography and Capillary Electrophoresis for Haemoglobin A2 Quantification: A Meta-Analysis - Wei, Yongzhong; Gu, Mingze; Su, Yuxin; Xi, Jiayun; Ren, Yuqing; Hu, Zhongshuang (Malaysian Journal of Medical Sciences, 2026)
Background: Haemoglobin A2 (HbA2) measurement is essential for diagnosing β-thalassemia carriers, yet even small analytical biases may affect clinical interpretation near the diagnostic threshold of 3.5%. High-performance liquid chromatography (HPLC) and capillary electrophoresis (CE) are widely used, but their agreement remains uncertain. The study aimed to systematically evaluate the measurement bias between HPLC and CE in HbA2 quantification.Methods: A systematic review and meta-analysis were conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Eligible studies directly compared HbA2 values measured by HPLC and CE in the same samples. Data on mean bias, standard deviation (SD), and limits of agreement (LoA) were extracted. A random-effects model was used to pool mean bias, and subgroup analyses were performed for normal individuals, β-thalassemia carriers, and haemoglobin variant carriers. Sensitivity analysis was conducted to assess robustness.Results: Ten studies with 1,881 paired measurements were included. After excluding datasets with clear co-elution interference, mainly haemoglobin E (HbE) and haemoglobin Hope (Hb Hope), the pooled mean bias was 0.16% (95% confidence interval [CI]: 0.03, 0.29), with high heterogeneity (I2 = 99.5). Subgroup analysis showed a mean bias of 0.37% (95% CI: 0.24, 0.50) in healthy individuals and 0.39% (95% CI: 0.20, 0.59) in β-thalassemia carriers. Sensitivity analysis confirmed the stability of the results.Conclusion: HPLC and CE demonstrate systematic but clinically relevant differences in HbA2 measurement, particularly near diagnostic thresholds. HbA2 measurement results obtained from HPLC and CE should not be used interchangeably, and method-specific interpretation and harmonisation efforts are warranted.